A Basic Competence Analysis of Textbook Entitled ‘Buku Bahasa Inggris untuk SMA/MA/SMK/MAK’ in 2013 Revised Curricula for 10th Grade of Senior High School - Ikrar Genidal Riadil (Faculty of Education and Teachers Training, 2020)
This study aimed to find out whether ‘Buku Bahasa Inggris untuk SMA/ MA/SMK/MAK’ textbook of the 11th grade at the first semester fulfilled syllabus points of the 2013 revised curricula. The researcher used descriptive qualitative research. The data would be gathered from document analysis of an English textbook entitled ‘Buku Bahasa Inggris untuk SMA/ MA/SMK/MAK’ published by KEMENTERIAN PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA 2017 of 10th grade senior high school. The ‘Buku Bahasa Inggris untuk SMA/ MA/SMK/MAK’ textbook had contented syllabus of basic competence and learning material. Each basic competence was delivered in certain exercises of four English skills. The learning materials were effectively comprised and support to develop the materials which understood about social function which made as text structures, cooperating tasks were presented and correlated the other rules of text structures, and language features were presented and developed based on proper and fit vocabulary, the pronunciation and intonation exercises are correlated grammar to support the materials of adverb, modals, connector, tenses, etc. It provided and developed suitable topics and multimedia using based on the syllabus guidance as well. On the other hand, this textbook had weakness about there were basic competence 3.6/4.6 and 3.8/4.8 which were not suitable and irregular. Each available basic competence was not deliver in certain exercises of four English skills some of them only have three skills for basic competence which was included social functions, text structures and language features, the skills for each basic competence are listening, reading, speaking, and writing, but in some basic competences they are only use three skills which is reading, speaking, and writing only.